1993
DOI: 10.1007/bf02888014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic observations on NK cell activity and IL-2 and IFNγ productionin vitro in patients on maintenance hemodialysis

Abstract: In order to study the immune function of patients on maintenance hemodialysis (MHD), we assayed NK cell cytotoxicity against K562 targets in 40 patients on MHD, and the production of IL-2 and IFN in peripheral blood mononuclear cells (PBMC) after PHA stimulation, in contrast to those in normal controls. The results showed that NK cell activity and IL-2 and IFN levels were markedly lower in the patients than in the controls. After a single dialysis, NK cell activity as well as IL-2 and IFN levels were elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In the CRF group, the serum level of sCD26 tended to be lower than that in the control group, and the serum level of sCD30 was significantly higher than that in the control group. Our results suggest that a low expression of CD26 and a high expression of CD30 in helper T cells were the same in the CRF group and in the HD group and support the observation that the amounts of Th1 cytokines released from peripheral blood mononuclear cells in HD patients were lower than those in controls [18, 19]. The secretion of Th2 cytokines released from peripheral blood mononuclear cells in HD patients was higher than that in controls; furthermore, the serum level of Th2 cytokines such as IL-4 was higher than that in the controls [20, 21].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the CRF group, the serum level of sCD26 tended to be lower than that in the control group, and the serum level of sCD30 was significantly higher than that in the control group. Our results suggest that a low expression of CD26 and a high expression of CD30 in helper T cells were the same in the CRF group and in the HD group and support the observation that the amounts of Th1 cytokines released from peripheral blood mononuclear cells in HD patients were lower than those in controls [18, 19]. The secretion of Th2 cytokines released from peripheral blood mononuclear cells in HD patients was higher than that in controls; furthermore, the serum level of Th2 cytokines such as IL-4 was higher than that in the controls [20, 21].…”
Section: Discussionsupporting
confidence: 73%
“…Recently, several reports have indicated that the Th1 and Th2 cytokine profiles are released from peripheral blood mononuclear cells in patients on HD [15, 16, 17]; however, these studies are not only labor-intensive and time-consuming, but are also thoroughly contrary to the other reports analyzed by the same methods [18, 19, 20, 21]. The analysis of the Th1/Th2 balance by measuring the serum soluble CD26 (sCD26) and soluble CD30 (sCD30) levels is a more rapid and simpler method.…”
Section: Introductionmentioning
confidence: 41%
“…In our study, the IFN-γ production was increased in the patients as compared with the controls. However, several studies show that the IFN-γ levels are lower in patients than in controls [40, 41, 42]. Furthermore, inducibility of the IL-2 gene is lost in HD patients, concomitant with decreased inducibility of IFN-γ mRNA [43].…”
Section: Discussionmentioning
confidence: 99%